2011
DOI: 10.31018/jans.v3i1.158
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of antioxidant activity of flower and seed oil of Azadirachta indica A. juss

Abstract: The present study on evaluation of antioxidant activity of the flowers and seed oil of Neem plant Azardirachta indica A. Juss revealed that the ethanolic extract of flowers and seed oil at 200 μg/ml producing the highest free radical scavenging activity i.e. 64.17±0.02% and 66.34±0.06% respectively. The Neem oil has the highest amount of total phenol content (132 μg/ml) which is responsible for highest percentage of inhibition of DPPH radical. In conclusion Neem flower and seed oil have potential for use in hu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
28
2
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(32 citation statements)
references
References 15 publications
(9 reference statements)
1
28
2
1
Order By: Relevance
“…Experimentation was made to evaluate the antioxidant activity of the flowers and seed oil of neem plant Azadirachta indica A. Juss. and results revealed that ethanolic extract of flowers and seed oil at 200 μ g/mL produced the highest free radical scavenging activity with 64.17 ± 0.02% and 66.34 ± 0.06%, respectively [ 26 ].…”
Section: Therapeutic Implications Of Neem and Its Various Ingrediementioning
confidence: 99%
“…Experimentation was made to evaluate the antioxidant activity of the flowers and seed oil of neem plant Azadirachta indica A. Juss. and results revealed that ethanolic extract of flowers and seed oil at 200 μ g/mL produced the highest free radical scavenging activity with 64.17 ± 0.02% and 66.34 ± 0.06%, respectively [ 26 ].…”
Section: Therapeutic Implications Of Neem and Its Various Ingrediementioning
confidence: 99%
“…The unsaponifiable fraction contains sterols and tocopherols (with b-sitosterol and g-tocopherol as the major sterol and tocopherol components, respectively) (Djibril et al, 2015). It also contains vitamin E, phenols, and many triterpenoids of which azadirachtin is the most well known and studied (Devi and Maji, 2011;Nahak and Sahu, 2011).…”
mentioning
confidence: 99%
“…The antioxidant activity of all the different extract samples is measured by the DPPH radical scavenging method (18) To support our antioxidant results previously also several antioxidant activities of neem (6,(19)(20)(21), tulsi (9,(22)(23)(24) and cow urine (5,(25)(26)(27) are studied. The synergistic antioxidant activity of tulsi, ginger, tea, and black pepper is studied by Gupta et al (28)…”
Section: Antioxidant Activitymentioning
confidence: 57%